Pengaruh Keterampilan Menyimak Terhadap Keterampilan Menulis Cerpen Siswa Kelas V SDN Juluk II Kecamatan Saronggi - Hidayat, Irfan Afri; M. Ridwan; Sama' (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to find out how much influence listening skills have on the short story writing skills of grade V students at SDN Juluk II Saronggi. This study uses a non-experimental quantitative method approach. The data collection technique used is a questionnaire or questionnaire. This research was tested using regression (simple) which is a statistical quantitative technique in predicting the value of an output of a bound variable based on one independent variable in a regression equation. Data analysis using IBM SPSS version 21 statistics. The results of this study obtained the results of the t-test of 4,828, showing that the variable X of listening skills had an effect on the significance of variable Y, namely the writing skills of short story writing of grade V students of SDN Juluk II, Saronggi District. The results of the data analysis obtained had a significance of 0.000 < out of 0.05, meaning that the variable X of listening skills had an effect on the significance of the variable Y of short story writing skills of grade V students of SDN Juluk II, Saronggi District. From these results, it is important for students to pay attention to common factors that often occur, then look for ways to practice listening and writing short story writing skills, so that the desired goals can be achieved properly.